Optimizing the Assistance in Zakat Pick-Up Services and Zakat Fund Distribution by BAZNAS Trenggalek - Widamayanti, Shinta Eka; Barira, Imelda Nurrahmatul; Pinasty, Rekananta Nasa; Nuraini, Risna Ahmad; Faiza, Nurlaili Adkhi Rizfa (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2024)
The widening economic gap is one of the social problems that need to be addressed effectively. Zakat, as one of the instruments of Islamic economics, has an important role in reducing this gap by channeling some of the wealth from muzakki to mustahik. This community service focuses on assisting zakat pick-up services and distributing zakat funds at BAZNAS Trenggalek, with the aim of optimizing the effectiveness of zakat collection and distribution to be more transparent and on target. The method used in this service includes four main stages: planning, selecting recipients, and implementation. At the planning stage, mapping of target areas and identification of prospective zakat recipients is carried out in accordance with the principles of 8 asnaf. The implementation stage includes zakat pick-up services for muzakki and distribution of zakat funds in the form of cash assistance or productive goods that can improve the welfare of mustahik. Evaluation is carried out to assess the effectiveness of the program and identify obstacles and improvements that can be applied in the future. The results of the service show that zakat pick-up services increase the participation of muzakki in paying zakat, while more targeted distribution of zakat funds has a significant impact on the welfare of mustahik. In addition, this mentoring provides students with direct experience in professional and accountable zakat management. With this approach, zakat is not only a short-term solution to overcoming poverty, but also an instrument for sustainable economic empowerment